2015
DOI: 10.1016/j.aju.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of outcome of percutaneous nephrolithotomy using the ‘STONE’ nephrolithometry score: A single-centre experience

Abstract: ObjectiveTo assess the prediction of stone clearance and complications of percutaneous nephrolithotomy (PCNL) using the ‘STONE’ nephrolithometry score, assessing stone size, tract length (skin-to-stone distance), degree of obstruction, number of calyces involved and stone essence (density).Patients and methodsThis was a prospective study of patients undergoing single-tract PCNL while prone, conducted at a university hospital. All patients had non-contrast-enhanced computed tomography within 3 weeks of the proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Thus, it is understandable why a model that is designed to optimally statistically predict SFR may not do well when applied to other outcomes. We thus find it not surprising when conflicting data exists for the association of ordinal, as well as the CROES score, with complications (with more favourable data for ordinal scores) [9,10,[13][14][15]19,21]. These conflicting reports can be explained by issues of sample size, variations in expertise, patient-related factors (comorbidities), and surgical approach characteristics.…”
Section: Scoring Systemmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, it is understandable why a model that is designed to optimally statistically predict SFR may not do well when applied to other outcomes. We thus find it not surprising when conflicting data exists for the association of ordinal, as well as the CROES score, with complications (with more favourable data for ordinal scores) [9,10,[13][14][15]19,21]. These conflicting reports can be explained by issues of sample size, variations in expertise, patient-related factors (comorbidities), and surgical approach characteristics.…”
Section: Scoring Systemmentioning
confidence: 92%
“…and CROES scores also found to be associated with complications), although cross-comparative studies have been fewer [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The only systematic review concluded with ambiguity over the clear superiority of any one system and recommended further validation studies [23].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, most patients who required additional postoperative procedures had staghorn or multiple calculi. Farhan et al 37 in their study found that among patients with residual stones, six (29%) had additional treatments, with shock-wave lithotripsy in four and semi-rigid ureteroscopy and JJ stenting in one each. Average hospital stay was 5.5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting complications and success of percutaneous surgery for urolithiasis can now be reliably done using one of the several nephrolithometry scores [22]. Nephrolithometry scoring systems are based on pre-operative stone and patient features and they demonstrate and stratify relationships between kidney's anatomy and stones.…”
Section: Ct Beyond the Diagnosis Of Stonementioning
confidence: 99%
“…Stone size, composition, location, skin to stone distance, etc. are some of the well recognised parameters used in the risk stratiication and predicting success of treatment [22].…”
Section: Ct Beyond the Diagnosis Of Stonementioning
confidence: 99%